Factors Associated With Cessation of Exclusive Breastfeeding Among Working Women - Kalimah Kalimah; Ermi Girsang; Putranto Manalu (Jurnal Ilmu Kesehatan Masyarakat, 2024)
Exclusive breastfeeding for the first six months are crucial for infant nutrition. The condition of mothers as workers is reported to be one of the factors that hinders exclusive breastfeeding, while the number of working mothers continues to increase every year. This study aimed to evaluate the level of exclusive breastfeeding and identify factors associated with the cessation of exclusive breastfeeding among working mothers. This research employed an analytical observational study. Data was collected from five health center areas in Langkat district, involving 165 working mothers. Samples were taken using a purposive sampling technique. Data analysis included univariate, bivariate (chi-square), and multivariate (logistic regression) analyses. This study reported low levels of exclusive breastfeeding among working mothers. Several factors were associated with breastfeeding, namely age (OR=2.13, 95% CI, 1.07-4.24); p=0.044), education (OR=2.40, 95% CI, 11.24-4.64; p = 0.009), knowledge (OR= 27.08, 95% CI, 10.88-67.37; p<0.001), attitude (OR=18.80, 95% CI,8.33-42.43; p<0.001) and husband's support (OR=8.14, CI 95%, 3.92-16.87; p<0.001). This study concluded that adequate knowledge, a positive attitude towards breastfeeding, and a husband's support are key factors for the success of exclusive breastfeeding for working mothers. Therefore, health workers must pay special attention to these aspects by providing education on the importance of breastfeeding for pregnant women and husbands by providing education of exclusive breastfeeding. It is suggested that future research design a model of public health education to increase the quality and quantity of exclusive breastfeeding among employed women.